Metabolic and Co-metabolic Degradation of Industrially Important Chlorinated Organics Under Aerobic Conditions - (:unkn) unknown (SPRINGER, 2010)
Chlorinated organic compounds are the frequently detected xenobiotics in industrial effluents. They may enter surface water, groundwater and soil systems. Examples are presented on the level of these Compounds in aquatic systems. The chapter then addresses the biological removal of these compounds by aerobic metabolism in which the substrate is used as an energy and carbon source. However, the major part of chlorinated organic compounds is resistant to metabolic removal. Yet, some can effectively be removed through aerobic co-metabolism in bioremediation of polluted groundwater and soil and in wastewater treatment systems. Ill aerobic co-metabolic removal of these compounds different types of substrates can be used as primary growth-substrates such as phenol, toluene, propane, methane, ammonia and others which are extensively reviewed ill this chapter. The basic features of natural and enhanced bioremediation are also outlined ill the chapter. The aerobic co-metabolism is exploited mainly for bioremediation of chlorinated aliphatic compounds such as trichloroethylene (TCE) in groundwater and ill sonic cases for chlorinated benzenes and phenols. Examples of field-, pilot- and laboratory studies are documented which deal with aerobic co-metabolic removal of chlorinated compounds.
Keywords: COMETABOLIC DEGRADATION; PHENOLIC-COMPOUNDS; ACTIVATED-SLUDGE; TRICHLOROETHYLENE DEGRADATION; POLYCHLORINATED-BIPHENYLS; ALIPHATIC-HYDROCARBONS; PSEUDOMONAS SP; BIODEGRADATION; KINETICS; 4-CHLOROPHENOL